The Pituitary-Thyroid Axis and Prolactin Secretion in Hemodialysis Patients in Two Endemic Regions of Eastern Germany - Rasche, Franz Maximilian; Rettig, Ronny; Frese, Thomas; Rasche, Wilma Gertrud; Barinka, Filip; Roesl, Guenter; Keller, Frieder; Lindner, Tom H.; Schneider, Jochen G.; Beige, Joachim; Ebert, Thomas; Schiekofer, Stephan (Experimental and Clinical Endocrinology & Diabetes, 2018)
Introduction Endocrine disorders of the pituitary axes are frequent in patients with hemodialysis (CKD5D). The aim of this multicenter study (Leipzig (L), Quedlinburg and Blankenburg in the Harz region (Hz)) in CKD5D patients was to evaluate influences of CKD5D related factors, morphological and biochemical parameters, and serum iodine and prolactin concentrations on the pituitary-thyroid axis.Patients and Methods 170 patients (L n=58; Hz n=112) were included in this prospective, non-interventional, cross-sectional study. Mann-Whitney-U-test and bivariate correlation analyses with Spearman-Rho test (r correlation coefficient) were used in statistical analysis.Results TSH was higher in patients with prolactin concentrations>370 mIU/l (p=0.013), in patients with high flux membranes (p=0.0013) and in patients with longer dialysis vintage (p=0.04). Median iodine serum concentrations were slightly elevated in the Leipzig cohort (p=0.001) and correlated with fT4 (p<0.001, r=0.43) and albumin (p=0.001, r=0.245) but not with morphological signs. Albumin was correlated with fT3 (p<0.001, r=0.339) and fT4 (p<0.001, r=0.421). Prolactin was correlated with residual excretion rate (p=0.001, r=- 0.303) and thyroid volume (p=0.027, r=0.217).Conclusions In the assessment of the thyroid status in CKD5D patients, the synopsis of the clinical and nutritional status, comorbidities, ultrasound of the thyroid gland and laboratory results is necessary for further intervention with hormone replacement. Standardized reference values of the pituitary-thyroid axis should be critically evaluated and are still lacking in CKD5D.
Keywords: pituitary-thyroid axis; TSH; fT3; fT4; iodine serum concentration; prolactin; hemodialysis; goiter; nodule